Recent Developments in Homogeneous Advanced Oxidation Processes for Water and Wastewater Treatment - M. Muruganandham; R. P. S. Suri; Sh. Jafari; M. Sillanpää; Gang-Juan Lee; J. J. Wu; M. Swaminathan (International Journal of Photoenergy)
This paper reports on recent developments in homogeneous Advanced Oxidation Processes (AOPs) for the treatment of water and wastewater. It has already been established that AOPs are very efficient compared to conventional treatment methods for degradation and mineralization of recalcitrant pollutants present in water and wastewater. AOPs generate a powerful oxidizing agent, hydroxyl radical, which can react with most of the pollutants present in wastewater. Therefore, it is important to discuss recent developments in AOPs. The homogeneous AOPs such as O3, UV/O3, UV/O3/H2O2, and UV/H2O2, Fe2+/H2O2, UV/Fe2+/H2O2 on the degradation of pollutants are discussed in this paper. The influence on the process efficiency of various experimental parameters such as solution pH, temperature, oxidant concentration, and the dosage of the light source is discussed. A list of contaminants used for degradation by various AOPs and the experimental conditions used for the treatment are discussed in detail.